Interaksi Habitus dan Modal Pendidikan: Strategi Manajerial Kepala Sekolah dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Anggraeni, Puput Nazil; Mulyono, Rahmat; Saryanto, Saryanto (Media Manajemen Pendidikan, 2025)
This study employs a qualitative approach with research subjects consisting of the school principal, Indonesian language teachers, and two student representatives from grades X, XI, and XII, selected through purposive sampling techniques. Data were collected through interviews, observations, and document studies. Data analysis was conducted in three stages: data condensation, data display, and drawing conclusions.The findings indicate that the principal’s role as a manager in elaborating habitus and educational capital is implemented by designing literacy and Indonesian language learning activities using learning strategies based on students’ cognitive structures. This is achieved through diagnostic assessments involving basic writing tests, learning processes that present concrete facts, and student engagement through contextual questions.